Frosty Feast Entreprise / Aiman Ghazali Shahrul Azlan … [et al.]. - Shahrul Azlan, Aiman Ghazali; Mohd Zainal, Ani Syazanna; Rodzi, Muhammad Aideed; Mohd Don, Nur Arfa; Abd Karim, Nur Dalila Safiyah
Frosty Feast Enterprise is a pioneering force in the ready-to-eat meal industry, dedicated to providing convenient, nutritious, and delicious meals for individuals with busy lifestyles. With a commitment to culinary excellence, Frosty Feast offers a diverse menu of chef-crafted ready-to eat meals, meeting the needs of various tastes and dietary preferences. The company distinguishes itself through a focus on quality, health, and innovation, making it a future leader in the ever-evolving landscape of quick and delightful dining experiences. The organizational structure comprises a team of five key personnel, including General Manager, Administration Manager, Marketing Manager, Operation Manager, and Financial Manager. The administration plan outlines a compensation and benefit structure, office equipment budget, and administrative budget. With a mission to provide high-quality, affordable, and nutritious ready-to eat meals, Frosty Feast aims to expand its market share through innovative marketing strategies and a commitment to fresh, locally sourced ingredients. Frosty Feast's marketing plan aims to enhance brand awareness, expand market reach, increase online sales, product line launches, customer loyalty, and sustainability efforts. The target markets are identified through demographic, psychographic, and geographic segmentation, with a focus on low and middle-income consumers. The plan emphasizes a value-based pricing strategy, quality assurance measures, features, design and diverse distribution channels, including direct-to consumer, retailers, wholesalers, and online platforms. The marketing team, comprising a Marketing Manager, Consultant, and Sale Promoter, operates within a well-allocated budget. Frosty Feast's operational plan outlines a meticulous process from raw material procurement to delivery, ensuring product quality and safety. The business operates in a strategically located facility, facilitating efficient supply chain management. Licensing and certification, including HACCP and Halal, are prioritized for compliance. Business and operational hours are established, and the operations budget covers fixed assets, monthly expenses, and other operational costs. The production planning involves average sales forecasts, material planning, supplier relationships, and equipment acquisition. The manpower planning includes salaries for the Operation Manager, workers, and a driver. With a production facility strategically located in Nilai, Negeri Sembilan, Frosty Feast aims for efficient operations and seamless supply chain management. The financial plan encompasses operational budgets such as administration, marketing, and operations. It provides details on project implementation costs, sources of financing, pro-forma cash flow, income statement, and balance sheet. Frosty Feast anticipates healthy financial growth by adhering to budgetary allocations, investing in strategic marketing, and ensuring efficient operational processes. In conclusion, Frosty Feast Enterprise stands poised to revolutionize the ready-to-eat meal industry by combining culinary excellence with unmatched convenience. With a robust administration, innovative marketing strategies, efficient operations, and a sound financial plan, Frosty Feast is positioned for sustained success in delivering delightful dining experiences to customers all over the world in the future.